2019
DOI: 10.1186/s11689-019-9284-y
|View full text |Cite
|
Sign up to set email alerts
|

Early negative affect in males and females with fragile X syndrome: implications for anxiety and autism

Abstract: Background Fragile X syndrome (FXS) is a genetic disorder that is highly comorbid with anxiety and autism spectrum disorder (ASD). Elevated negative affect in young children has been associated with increased risk for both anxiety and ASD; however, these relations remain poorly understood in FXS. Methods The present prospective longitudinal study examined the trajectory of negative affect from infancy through preschool in males and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 56 publications
5
18
0
3
Order By: Relevance
“…The IBQ-R was normed on a neurotypical diverse sample of mother-child dyads and produced satisfactory internal consistency. The IBQ-R has been used widely across multiple samples of individuals with neurodevelopmental disabilities [ 30 , 38 ]. While the IBQ-R has not been factor analyzed with a sample of infants with FXS, the factor structure of the Child Behavior Questionnaire (CBQ; which is the version of the temperament questionnaire designed for children between 3 and 7 years old, who have aged out of the IBQ) was investigated in FXS and found to follow a similar structure as the normative data [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IBQ-R was normed on a neurotypical diverse sample of mother-child dyads and produced satisfactory internal consistency. The IBQ-R has been used widely across multiple samples of individuals with neurodevelopmental disabilities [ 30 , 38 ]. While the IBQ-R has not been factor analyzed with a sample of infants with FXS, the factor structure of the Child Behavior Questionnaire (CBQ; which is the version of the temperament questionnaire designed for children between 3 and 7 years old, who have aged out of the IBQ) was investigated in FXS and found to follow a similar structure as the normative data [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that children with FXS display increased distress, gaze aversion, and avoidance during a social challenge task [ 27 , 28 ]. Emerging evidence also suggests that elevated negative affect, a broader temperament profile that encompasses behavioral inhibition, in preschool-aged children with FXS is associated with anxiety symptoms later in development [ 29 , 30 ]. Of note, this work has shown that elevated negative affect is selective in predicting anxiety symptoms and not features of autism spectrum disorder in FXS, which is important given that anxiety and autism spectrum disorder share features and are both commonly diagnosed in FXS [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these known contributors to heterogeneity, very few eye‐tracking studies include females in their sample of FXS (Crawford et al, 2016; Hong et al, 2019). Further, much research in FXS has highlighted dynamic trajectories across many domains in FXS, including behavioral, cognitive, and neural development, showing that many traits are not stable over time, and may contribute to clinical symptoms differentially at different ages (Baranek et al, 2008; Caravella & Roberts, 2017; Shen et al, 2022; Tonnsen et al, 2015; Wall et al, 2019). Nevertheless, studies on social attention in FXS utilize a wide age sample that could potentially mask developmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Macari et al ( 25 ) found that 26-month-old toddlers with non-syndromic autism (nsASD) have higher overall negative affect than their NT peers; this elevation was unique to nsASD and not observed in a matched group of developmentally delayed toddlers without nsASD. Using a developmental approach, studies of negative affect have shown that children with FXS demonstrate an accelerated increase in negative affect over time as compared to their NT peers ( 27 , 28 ), despite cross-sectional studies showing that children with FXS have lower negative affect at certain ages ( 29 ). No study to date has directly compared negative affect in children with nsASD contrasted to FXS, leaving an important gap in our understanding of the role negative affect plays in the differential characterization of these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Infants and toddlers with FXS exhibit atypical longitudinal patterns of facial and behavioral social fear and these patterns are associated with withdrawal symptoms associated with social anxiety ( 55 ). Further, prospective longitudinal studies have shown that early negative affect predicts anxiety symptoms in males ( 28 ) and females ( 27 ) with FXS. In older children, RSA dysfunction is associated with pragmatic language deficits common in autism in older boys with nsASD, but not autism severity ( 40 ).…”
Section: Introductionmentioning
confidence: 99%